2006
DOI: 10.1111/j.1440-1681.2006.04436.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perindopril and Hydrochlorothiazide on Selected Indices of Oxidative Stress in the Blood of Elderly Patients With Essential Hypertension

Abstract: 1. The aim of the present study was to determine the effect of hypotensive therapy with a diuretic (hydrochlorothiazide) and an angiotensin-converting enzyme inhibitor (perindopril) on selected oxidative stress parameters in the blood of elderly patients with essential hypertension. 2. Studies were performed in 45 elderly patients with essential hypertension at baseline and after the 45th day of perindopril (n = 25) or hydrochlorothiazide (n = 20) therapy, as well as in 25 young and 25 elderly normotensive sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Our finding of elevated plasma levels and renal excretion of HODE in patients with essential hypertension extends prior reports in essential hypertension of increased plasma levels of the ROS markers of hydrogen peroxide (22), plasma protein carbonyl derivatives (19,40), and lipid peroxidation products (9,10,19,28,36,37,38,43), oxidized to reduced ratio of glutathione (26,27,38) and O 2 ⅐ Ϫ in activated polymorphonuclear leukocytes (21,25,37,53). However, other studies have failed to detect an increase in renal excretion of lipid peroxidation products (11) or ROS in lymphocytes (30) in hypertensive subjects.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our finding of elevated plasma levels and renal excretion of HODE in patients with essential hypertension extends prior reports in essential hypertension of increased plasma levels of the ROS markers of hydrogen peroxide (22), plasma protein carbonyl derivatives (19,40), and lipid peroxidation products (9,10,19,28,36,37,38,43), oxidized to reduced ratio of glutathione (26,27,38) and O 2 ⅐ Ϫ in activated polymorphonuclear leukocytes (21,25,37,53). However, other studies have failed to detect an increase in renal excretion of lipid peroxidation products (11) or ROS in lymphocytes (30) in hypertensive subjects.…”
Section: Discussionsupporting
confidence: 78%
“…A second limitation is that patients with essential hypertension were receiving antihypertensive therapy until 24 h before study, as required by our institutional Human Subjects Review Group. However, prior reports have shown that the treatment of hypertension with an angiotensin receptor blocker (12,14,16,26,52), an angiotensin-converting enzyme inhibitor (12,16,19,28,52), or a calcium channel blocker (13,26,37,53) all reduce plasma levels of oxidative stress markers (13,14,19,26,28,37,52,53) or ADMA (12,16,52). Thus, the elevated plasma levels of ADMA and HODE are not likely a consequence of prior treatment of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Since hydrochlorothiazide alone is incapable of reducing superoxide [20] or increasing SOD activity [21] , the increased SOD activity after the add-on thiazide, but not after the add-on amlodipine might result from the enhanced blockade of the renin-angiotensin system by the combination therapy with valsartan plus hydrochlorothiazide. However, the increase in serum SOD activity was not associated with changes in PWV or UAE.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chlorthalidone and indapamide have been shown to have more potent antioxidant effects than other thiazides (11,12). Another report showed that HCTZ does not significantly decrease the erythrocyte MDA concentrations in hypertensive patients (13). Another reason may be that antihypertensive drugs, such as ARBs, calcium antagonists, β-blockers and α-blockers, themselves have an antioxidant effect (14)(15)(16)(17) that possibly obscures the antioxidant effects of thiazide diuretics.…”
Section: Discussionmentioning
confidence: 99%